Consuming Ecstasy: Representations of Male and Female Orgasm in Mainstream Pornography - Séguin, Léa J.; Rodrigue, Carl; Lavigne, Julie (The Journal of Sex Research, 2018)
Social representations, which appear in a variety of media, can influence the way sexual experiences are perceived and understood. While pornography is not the only medium in which orgasm is portrayed, it is the most explicit, and it is widespread and easily accessible. As such, pornography is an ideal medium for examining representations of male and female orgasm. PornHub’s 50 most viewed videos of all time were viewed and coded for the frequency of male and female orgasm, orgasm-inducing sex acts (and whether activity inducing female orgasms included some form of clitoral stimulation), and auditory (verbal, vocal) and visual (bodily) indicators of orgasm. Content analysis was used to code and analyze the data. Results were analyzed in light of sexual script theory and previous orgasm research. Only 18.3% of women, compared to 78.0% of men, were shown reaching orgasm. Sex differences in depictions of orgasm, beyond the appearance of semen, were documented. Results support the male performance script as evident in pornographic depictions of orgasm, as well as coital and orgasm imperatives. As a result, representations of male and female orgasm in mainstream pornography may serve to perpetuate unrealistic beliefs and expectations in relation to female orgasm and male sexual performance.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; cours; discipline; orgasme; premier cycle; périodes historiques; rapports sociaux de sexe; représentation; ressource en ligne; sciences humaines; sex1911; sexologie; sexualité; thématiques

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

L'invention de l'hétérosexualité - Katz, Jonathan (EPEL, 2001)
L'auteur retrace l'histoire du concept d'hétérosexualité. Il analyse les textes d'auteurs comme Freud, Richard von Krafft-Ebing, Michel Foucault, Betty Friedan ou Kate Millet. Il nous montre que la distinction homosexuel/hétérosexuel ne repose pas sur une nature immuable mais constitue une façon récente de classer et de juger la société. [SDM].
Section: 236 pages ; 21 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; analyse de discours; approches et analyses; cours; discipline; discours dominant; europe; france; his4860; histoire; histoire et politique; homosexualité; hétérosexisme; hétérosexualité; identité sexuelle; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sex1181; sex1183; sexologie; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; épistémologie

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Section: xviii, 278 p
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Les constructions sociales de la sexualite - Bozon, Michel; Leridon, Henri (Population (French Edition), 1993)
Keywords: 1900-1999; approches et analyses; cours; discipline; premier cycle; production des savoirs; périodes historiques; rapports sociaux de sexe; sciences humaines; sciences sociales; sex1183; sexologie; sexualité; thématiques; épistémologie

Un choix sans equivoque : recherches historiques sur les relations amoureuses entre les femmes : XVIe-XXe siecle - Bonnet, Marie-Jo (Denoël, 1981)
C'est le fruit de recherches menées pour une thèse de doctorat de 3e cycle. Etude détaillée, même érudite, mais de lecture facile. Importante bibliographie.
Section: 293 pages
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; LGBTQIA2+; amour lesbien; approches et analyses; cours; discipline; discours dominant; his4860; histoire; histoire de la sexualité; histoire des femmes*; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexologie; sexualité; sexualité lesbienne; sexualités dissidentes; systèmes d'oppressions; thématiques